Structural associations of symptomatic knee osteoarthritis - Wyatt, Laura A. (2015)
Background: Pain is the major symptom of osteoarthritis (OA), however, the link between OA knee pain and pathology is incompletely understood. Furthermore, the earliest pathological changes in OA are difficult to characterise. The major aim of this thesis was to better understand the role of knee joint pathology in OA pain.